The Influence of Financial Attitudes, Financial Literacy, and Income Level on Informal Sector Financial Management Behavior among Basic Food Traders in Praya City, Lombok Tengah - Sejati Ratna Sari; Ida Ayu Putri Suprapti; Peter J. Morgan (Economy and Finance Enthusiastic, 2024)
MSME are a form of business managed by a person or group of people with a certain amount of capital and setting up a business with the aim of making a profit with the ability to develop flexible business processes. This research aims to determine the influence of financial attitudes, financial literacy, and income level on informal sector financial management behavior among basic food traders in Praya City, Central Lombok. The sample used was 103 respondents. The sampling technique uses probability sampling. In explaining the research results, the data analysis technique uses Structural Equation Model (SEM) analysis based on Partial Least Square (PLS). The research results show that the financial attitude and income level variables with financial management behavior have a positive relationship with financial management behavior and do not have a significant effect. However, the financial literacy variable shows a positive relationship and has a significant effect on financial management behavior. This implies that an individual's financial decisions will be greatly influenced by their financial knowledge.